Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1021/jp9800261
|View full text |Cite
|
Sign up to set email alerts
|

Interrogation of Nanoscale Silicon Dioxide/Water Interfaces via Hyper-Rayleigh Scattering

Abstract: Hyper-Rayleigh scattering (HRS) experiments performed on nanometer-scale SiO2/water interfaces (aqueous colloidal suspensions) display finite, measurable signals. HRS is not constrained by the orientational, size, and/or charge restrictions inherent to conventional interfacial second harmonic generation (SHG) or electric-field-induced SHG measurements. Thus, apparently for the first time, the second-order nonlinear optical (NLO) response of ultrasmall interfaces has been measured. pH- and electrolyte-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
29
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 28 publications
3
29
1
Order By: Relevance
“…This work follows several recent reports of substantial HRS from nanocrystalline gold particle suspensions [7][8][9][10] and reports of SHG from highly concentrated gold nanoparticle samples [11,12]. HRS signals from gold nanoparticles were observed to exceed by factors of up to 10 5 those observed from suspensions of similarly sized wide bandgap semiconductor particles [13] and silicondioxide insulator particles [14]. The SHG study showed conclusively, via excitation profile measurements, that the nonlinear response is dramatically enhanced by resonance interactions with the gold plasmon band.…”
Section: Introductionsupporting
confidence: 89%
“…This work follows several recent reports of substantial HRS from nanocrystalline gold particle suspensions [7][8][9][10] and reports of SHG from highly concentrated gold nanoparticle samples [11,12]. HRS signals from gold nanoparticles were observed to exceed by factors of up to 10 5 those observed from suspensions of similarly sized wide bandgap semiconductor particles [13] and silicondioxide insulator particles [14]. The SHG study showed conclusively, via excitation profile measurements, that the nonlinear response is dramatically enhanced by resonance interactions with the gold plasmon band.…”
Section: Introductionsupporting
confidence: 89%
“…[27][28][29]. The conflicting estimates of the ratios of silanol groups with different structural motifs [25][26][27][28][29] likely reflect the difficulty brought about by the tendency of liquid water to react with crystalline silica. [20] One indisputable experimental finding is that the silanol surface density is σ SiOH ≈ 4.6 nm −2 on well-soaked amorphous Oxygen, silicon, and hydrogen atoms are colored in yellow, red, and white, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[16,[22][23][24] On the other hand, the Q 2 :Q 3 ratio has also been described as either approximately 1:4 or 4:1, which has prompted assignment of the pK a =4.5 SiOH group to either Q 2 (Refs. 25,26) or Q 3 (Refs. [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…There are at least two types of silanol groups at the water/silica interface characterized by a dissociation p K a of 4.5–6.5 for about 20% of the silanol sites, and a p K a value of 8.5–9.0 for the remaining 80% (6–13). The p K a values were associated with the geminal and single silanols, respectively (14,15).…”
Section: Introductionmentioning
confidence: 99%